1978
DOI: 10.1090/s0002-9939-1978-0493166-7
|View full text |Cite
|
Sign up to set email alerts
|

On multipliers of Segal algebras

Abstract: Abstract. Let T be a multiplier of a Segal algebra S on a locally compact abelian group G. We prove that T2(S) is closed if and only if T is a product of an idempotent and an invertible multiplier. We also show that the techniques developed in the proof of this theorem can be used to obtain some other known results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…These facts generalize many of the results appearing in the literature (e.g. [2], [4], [7], [8]), and they all are a consequence of the absence of l.a.p. or l.w.a.p.…”
Section: Now { a T:aeg}supporting
confidence: 86%
“…These facts generalize many of the results appearing in the literature (e.g. [2], [4], [7], [8]), and they all are a consequence of the absence of l.a.p. or l.w.a.p.…”
Section: Now { a T:aeg}supporting
confidence: 86%
“…Another interesting special case of Theorem 4.2 arises when 7 G M (A) is injective. We present here a new proof of a result, first noted for Tauberian algebras by Ransford, which in turn was a generalization of the same result for isometric multipliers on Tauberian regular algebras, noted by several authors, e.g., [DT,Theorem 2;ELN,Proposition 8]. Proof.…”
Section: Adding Regularity As An Assumptionsupporting
confidence: 64%
“…(T is a multiplier of B if T is a linear operator satisfying T(fg) = / • Tg for /, g G B.) In this note we show that the regularity conditions used in [1] and [2] are unnecessary. SpecificaUy we prove the following.…”
mentioning
confidence: 95%
“…In [1] and [2] it was shown that if a commutative semisimple Banach algebra B satisfies certain regularity conditions and if the maximal ideal space of B contains no isolated points, then every compact multiplier of B is trivial. (T is a multiplier of B if T is a linear operator satisfying T(fg) = / • Tg for /, g G B.)…”
mentioning
confidence: 99%